International Trade : What Everyone Needs to Know - Krueger, Anne O. (New York : Oxford university press, 2021)
"In all countries, there are laws and regulations affecting private economic activity. They are necessary to enable private economic activity to thrive, as well as to provide for honesty in information), consumer protection, and much more.
Includes Bibliographical references and index.
Keywords: Economics; Politics and Government; Business